Shape‐Shifting Patchy Particles. Issue 20 (12th April 2017) - Zheng, Xiaolong; Liu, Mingzhu; He, Mingxin; Pine, David J.; Weck, Marcus
Abstract: A facile method to synthesize shape‐shifting patchy particles on the colloidal scale is described. The design is based on the solvent‐induced shifting of the patch shape between concave and convex features. The initial concave patchy particles were synthesized in a water suspension by a swelling‐induced buckling process. Upon exposure to different solvents, the patches were tuned reversibly to be either concave or convex. These particles can be assembled into chained, branched, zigzag, and cyclic colloidal superstructures in a highly site‐specific manner by surface–liquid capillary bridging. The biphasic nature of the particles also enables site‐selective surface functionalization. Abstract : Shape of You : Shape‐shifting particles were developed on a colloidal scale. The design is based on the solvent‐induced shifting of the patch shape between concave and convex features. These so‐called patchy particles can be assembled into larger architectures in a site‐specific patch‐to‐patch manner by surface–liquid bridging where concave patches swell and protrude.